Effective nonlinear parameter measurement using FWM in optical fibers in a low power regime - Silva, Nuno Alexandre
The four-wave mixing (FWM) process in a low power regime is studied both theoretically and experimentally. The coupled-equations for the complex amplitudes are derived and solved. The proposed model is compared with experimental data. Results shows the need of considering both nonlinear and polarization dependent effects in order to obtain an accurate description of the four-wave mixing process in a low power regime. The effective nonlinear parameter is experimentally measured in a dispersion-shifted fiber, and the transition region between an almost co-polarized situation to a decorrelated state of polarization is observed.